The hidden worms on the beach: interstitial Syllidae (Annelida) from the Indo-Pacific - San Martín, Guillermo; Lucas, Yolanda; Westheide, Wilfried (Proceedings of the Biological Society of Washington, 2021)
Based on collections of interstitial Syllidae (Annelida) from several areas of the Indo-Pacific Ocean (Madagascar, Andaman Islands, South China, Hong-Kong, the Philippines, and New Zealand), we report a total of 49 species belonging to 19 genera. Most of these species are already known in the Indo-Pacific area, but these reports extend their distributional ranges. Nine species are described as new: Parexogone javieri (from New Zealand), Parexogone viejoi (from the Philippines), Prosphaerosyllis fittoni, Sphaerosyllis dieteri, Syllis kai, Perkinsyllis tsilo (from Madagascar), and Megasyllis chiki, Syllis dominguezi, and Syllis escribanoi (from China). Two species, previously described as Streptosyllis Webster & Benedict, 1884 are transferred to the genus Streptospinigera Kudenov, 1983: S. baolingi (Ding & Westheide, 1994), new combination, and S. hainanensis (Ding & Westheide, 1994), new combination, both from China. One species is transferred to Syllis [Typosyllis botosaneanui (Hartmann-Schr¨oder, 1973)], new combination.
World Polychaeta Database (WPolyD).